2017
DOI: 10.1177/2150131917736634
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Primary Care Provision to Medicare Beneficiaries by Physicians, Nurse Practitioners, or Physician Assistants: 2008-2014

Abstract: Objectives: To document the temporal trends in alternative primary care models in which physicians, nurse practitioners (NPs), or physician assistants (PAs) engaged in care provision to the elderly, and examine the role of these models in serving elders with multiple chronic conditions and those residing in rural and health professional shortage areas (HPSAs). Design: Serial cross-sectional analysis of Medicare claims data for years 2008, 2011, and 2014. Setting: Primary care outpatient setting. Participants: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…[1][2][3] Currently, APPs have become fixtures in the clinical setting, serving a critical role across the spectrum of medical disciplines, from delivery of primary care in rural settings to assisting in the operating room in highly specialized surgery. [4][5][6][7][8][9][10][11] There have been numerous studies examining the impact of APPs, with the majority demonstrating equivalent financial and clinical outcomes between teams that do employ APPs and those that do not. 12,13 Other studies quantifying the effects of APPs in field found APPs increase the efficiency of attending surgeons.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…[1][2][3] Currently, APPs have become fixtures in the clinical setting, serving a critical role across the spectrum of medical disciplines, from delivery of primary care in rural settings to assisting in the operating room in highly specialized surgery. [4][5][6][7][8][9][10][11] There have been numerous studies examining the impact of APPs, with the majority demonstrating equivalent financial and clinical outcomes between teams that do employ APPs and those that do not. 12,13 Other studies quantifying the effects of APPs in field found APPs increase the efficiency of attending surgeons.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Surprisingly, there was no evidence that more appointments were scheduled with APs in rural areas, which conflicts with 2 recent studies. 9,10 The differences may be driven by our smaller sample of rural practices and alternative research design-Xue et al 10 used Medicare claims data and Barnes et al 9 used proprietary practice-level data. Those studies, however, did not control for county-level characteristics such as race/ethnicity and income, and perhaps those characteristics are driving AP appointments more than rurality.…”
Section: Discussionmentioning
confidence: 99%
“…The strategy of “moving knowledge” instead of “moving patients” has been shown to be effective in managing other chronic diseases in medically underserved areas using the Extension for Community Health Outcomes model for telementoring . Many rural areas have been federally designated as medically underserved in part because primary care there is provided by other health professionals, including nurse practitioners and physician assistants . Increasing the availability of other professionals, such as respiratory therapists, would provide important services to patients and families affected by COPD such as training in the use of inhalers, and delivery of PR, which improves patient clinical COPD outcomes but requires continued physical activity after initial program completion .…”
Section: Goal 2: Improve the Prevention Diagnosis Treatment And Mamentioning
confidence: 99%
“…11,12 Many rural areas have been federally designated as medically underserved in part because primary care there is provided by other health professionals, including nurse practitioners and physician assistants. 13 Increasing the availability of other professionals, such as respiratory therapists, would provide important services to patients and families affected by COPD such as training in the use of inhalers, 14 and delivery of PR, which improves patient clinical COPD outcomes but requires continued physical activity after initial program completion. 15 These therapies are underutilized due to insufficient funding, resources, and reimbursement but also lack of awareness and knowledge by health care professionals, payors, and patients, 15 and their delivery is often complicated by the long distances that rural COPD patients must travel to access them.…”
Section: Goal 2: Improve the Prevention Diagnosis Treatment And Mamentioning
confidence: 99%